(−)-Epicatechin gallate blocked cellular foam formation in atherosclerosis by modulating CD36 expression in vitro and in vivo. Issue 5 (14th February 2023) - Yu, Jinjin; Zhou, Lili; Song, Huixin; Huang, Qiuxia; Yu, Jiabao; Wang, Siqi; Zhang, Xinya; Li, Weifeng; Niu, Xiaofeng
Abstract : ECG blocked the expression of ox-LDL receptor protein CD36 in HFD-induced aortic root plaques at different stages, and blocked inflammation, oxidative stress and cell foaming through Nrf2 and NF-κB signaling pathways. Abstract : Green tea is popular worldwide, so its main active ingredients have attracted people's attention. (−)-Epicatechin gallate (ECG) is the main active component of green tea polyphenols, which has good antioxidant activity, but its cardiovascular intervention is unknown. This study established in vitro and in vivo models of ox-LDL-induced macrophages and HFD-induced ApoE −/− mice to study the effects of ECG on atherosclerotic lesions. Firstly, the study confirmed that ECG has a therapeutic effect in different stages of atherosclerotic plaques. Subsequently, the results showed that the ox-LDL-induced release of pro-inflammatory mediators and the expression of the related protein CD86 in macrophages were inhibited by ECG. ECG blocked the formation of cellular foam by downregulating the expression of CD36 and LOX-1 proteins, thereby increasing SOD activity and reducing MDA production in cells. ECG also prevented ox-LDL-induced apoptosis, promoted macrophage migration, and increased plaque stability. The results confirmed that ECG attenuated ox-LDL-induced green fluorescence of ROS in macrophages by inhibiting the expression of related proteins in the NF-κB signaling pathway and activating the HO-1/Nrf2 signaling pathway. These results indicated that ECG has anti-oxidative stress and anti-inflammatory potential, and its molecular mechanism may be related to the inhibition of intracellular NF-κB signaling pathway proteins and activation of the HO-1/Nrf2 signaling pathway.